Industrial practice platform based on work-based learning: A solution to improve student competence - Suyitno Suyitno; Dwi Jatmoko; Aci Primartadi; Zahidah Ab-Latif (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2023)
This study aims to (1) Develop a work-based learning-based industrial practicum platform; (2) Know the feasibility of a work-based learning-based industrial practicum platform; and (3) Know whether there is an effectiveness of student learning with a work-based learning-based industrial practicum platform. This type of research is Research and Development (R&D) with the Four-D model, and the research subjects are class C students as an experimental class with a total of 21 students and class B students as a control class with a total of 22 students. Data collection uses a questionnaire method to determine the feasibility of the media used for research and written test questions in the form of multiple choice with a total of 20 questions. The data analysis test used a normality test, homogeneity test, and t-test. The research data showed that: (1) The procedure for developing practical learning media based on work-based learning includes the defining stage, planning stage, development stage, and dissemination stage; (2) Work-based learning media is feasible to use as a learning media in light vehicle electrical maintenance subjects. This can be proven from the validation results of media expert lecturers who showed 82.50% of the score indicating valid criteria. Validation by material expert lecturers showed 78.75% of the score obtained, indicating quite valid criteria; and (3) The t-test results (t-count = 6.021 and p = 0.000) prove that the work-based learning-based practicum platform made is effective for improving student learning outcomes. This is shown through the response of trial students, which includes small group trials, obtaining 77%, which includes five students, and large group trials, obtaining 80.50%, which includes 15 students. The normality test obtained p = 0.059 in the control class and p = 0.115 in the experimental class because p> 0.05 indicates that both groups are normally distributed. Through the homogeneity test, F count = 0.762 with p = 0.388 because p > 0.05, the two groups have homogeneous variants. Thus, the industrial platform practice based on work-based learning can improve student learning outcomes.